Open Science and Single-Case Design Research. (October 2022) - Cook, Bryan G.; Johnson, Austin H.; Maggin, Daniel M.; Therrien, William J.; Barton, Erin E.; Lloyd, John Wills; Reichow, Brian; Talbott, Elizabeth; Travers, Jason C.
Research indicating many study results do not replicate has raised questions about the credibility of science and prompted concerns about a potential reproducibility crisis. Moreover, most published research is not freely accessible, which limits the potential impact of science. Open science, which aims to make the research process more open and reproducible, has been proposed as one approach to increase the credibility and impact of scientific research. Although relatively little attention has been paid to open science in relation to single-case design, we propose that open-science practices can be applied to enhance the credibility and impact of single-case design research. In this article, we discuss how open-science practices align with other recent developments in single-case design research, describe four prominent open-science practices (i.e., preregistration, registered reports, data and materials sharing, and open access), and discuss potential benefits and limitations of each practice for single-case design.